The distribution of Apis laboriosa revisited: range extensions, biogeographic affinities, and species distribution modelling - Otis, Gard W.; Huang, Man-Juan; Kitnya, Nyaton; Sheikh, Umer Ayyaz Aslam; Faiz, Abu ul Hassan; Phung, Chinh H.; Warrit, Natapot; Peng, Yan-Qiong; Zhou, Xin; Oo, Hlaing Min; Acharya, Namoona; Devkota, Kedar (Frontiers in Bee Science, 2024)
Introduction Apis laboriosa, the Himalayan giant honeybee, inhabits the foothills of Himalaya and neighboring mountainous regions. Here we revise its distribution in light of recent reports and discoveries, review the ecozones it inhabits, and reassess its likely distribution through species distribution modeling. Methods We revised the range map for A. laboriosa by mapping locality records from various sources: refereed research publications, museum specimens, records with identifiable images of bees in publicly available databases, personal observations of the authors, and photos/videos and their coordinates submitted to the authors by honey-hunters, beekeepers, and extension workers. We then used that map to determine the ecozones in which the species occurs. The geographical coordinates of the data localities were used to estimate the potential suitable areas for the bee with MaxEnt modeling. Results Our research filled in several previously identified gaps in the distribution of A. laboriosa: in western Nepal; mountainous regions of Myanmar, northwestern Thailand, and northern Laos; several river valleys in Xizang and Yunnan, China; and northeastern Pakistan. Over most of its range this bee species primarily occupies subtropical broadleaf forests with strong Himalayan affinities. However, in the western part of its range it extends into zones dominated by conifers. The sites where A. laboriosa has been recorded closely match the predicted range of the species. Two variables, mean temperature of the coldest quarter and temperature seasonality, contributed most (76%) to the species distribution model. Discussion Apis laboriosa has a more extensive distribution in the foothills of the Himalaya and neighboring mountainous regions than has been previously recognized. The range now extends from longitude 74.4°–105.9°E, a linear distance of 3300 km, and from latitude 19.2°N–34.8°N. We have documented nesting on tree branches in northern Vietnam. Future research is warranted on its elevational migrations along river valleys, population differentiation, and ecological role as a pollinator in the different ecological zones it inhabits.